Study on crystalline structure of poly(vinylidene fluoride)/polyethylene/graphene blend‐nanocomposites. Issue 11 (17th May 2019) - Rafeie, Omid; Razavi Aghjeh, Mir Karim; Tavakoli, Akram; Salami‐Kalajahi, Mehdi; Jameie‐Oskooie, Amin; Ghayoumi, Mansour
Abstract: Effect of graphene nano‐platelets (GnP) on the crystalline structure of poly(vinylidene fluoride)/polyethylene (PVDF/PE) blends was studied. The PVDF/GnP were melt compounded with PE and/or PE/PE‐g‐MA mixture to obtain the desired compositions. Alteration in polymorphism of the PVDF component in the blends and in the presence of GnP, was evaluated employing different analyses. The flow‐induced crystallization experiments were conducted under oscillating rheometry at vicinity of crystallization temperature of the PVDF. The results of XRD and FTIR analysis indicated that the charge‐transfer CF bonding interaction between the PVDF chains and basal plane of GnP layers led to alteration of polymorphism of PVDF from α form to α‐, γ‐, and β‐phase crystals. Selective localization of the GnP in PVDF component increased the CF bonding interaction and decreased the hydrogen bonding between PVDF and PE chains, respectively. In the presence of PE‐g‐MA, the hydrogen bonding promoted and the CF bonding interaction decreased leading to predominance of the α‐form crystal formation in the PVDF phase. While the GnP acted as nucleating agent in PVDF component under quiescent conditions, it had negative effect on row nuclei under flow conditions. The structures originated from row‐nuclei and GnP surfaces, led to formation of "shish‐kebab" and "oriented lamella" morphologies, respectively.